(untitled) (Swiss Medical Weekly, 2024)
OBJECTIVES: Colorectal carcinoma remains one of the most common malignancies worldwide. Colonoscopy screening is most effective for early detection and tumour prevention and is currently recommended in Europe for adults aged over 50 years. However, given that an increasing proportion of patients are diagnosed before the age of 50, we set out to determine the detection rate of colorectal carcinoma in patients younger than 50 years and to determine the best threshold for starting colonoscopy screening. METHODS: Single-centre, retrospective cohort study of all colonoscopies performed, regardless of indication, in our department at a tertiary Swiss university hospital in patients aged ≥18 and <60 years between 2016 and 2021. Colorectal cancer detection rate was calculated per 5-year age group and analysed separately by sex. RESULTS: The current analysis included 2846 colonoscopies performed for any indication. Colorectal carcinoma was found in 5/366 (1.4%) patients aged 45–49 years (3/210 or 1.4% of males and 2/156 or 1.3% of females) and in 9/819 (1.1%) patients aged 50–54 years (5/495 or 1.0% of males and 4/324 or 1.2% of females). Adenomas with high-grade dysplasia were found in 5/366 (1.4%) patients aged 45–49 years and in 11/819 (1.3%) aged 50–54 years; by sex, in 4/210 or 1.9% of males and 1/156 or 0.6% of females aged 45–49 years, and in 6/495 or 1.2% of males and 5/324 or 1.5% of females aged 50–54 years. Detection of adenoma with low-grade dysplasia increased from 14.6% (21/144) at age <30 years to 41% (150/366) at 45–49 years and 43.5% (356/819) at 50–54 years. A similar increasing trend was also seen if we analysed these groups by sex. CONCLUSIONS: The detection rate of colorectal carcinoma, but also adenomas, in our patients aged 45–49 years was similar to that in patients aged over 50, in both sexes. Thus our data are in line with the assumption that lowering the screening age to 45 years might be reasonable from a medical point of view for achieving a reduction in disease-specific mortality by improved screening strategies.